Mating tactics and male–male courtship in the lek-breeding cichlid Oreochromis mossambicus - Oliveira, Rui Filipe (2012)
Data are presented on the breeding behaviour of Oreochromis mossambicus under captive conditions. Males tended to synchronize their occupation of territories and breeding activities. Different male mating tactics were observed, namely establishing a breeding territory, acting as a floater, or behaving as a sneaker. The majority of spawnings observed involved dominant males and were subjected to interference from other males. Males were found to court other males that frequently responded to these attempts by adopting a female-like behaviour. Results are discussed in terms of a probable time constraint in territoriality, which promotes male–male competition and a low level of sex discrimination by territorial fish.